Perahu dan Rumah Gadang: Bagian Budaya Kayu di Sekitar Danau Singkarak, Sumatera Barat - Hidayati, Dyah; Susilowati, Nenggih (PURBAWIDYA, 2024)
The environment of Lake Singkarak provides natural resources to be utilized by human around it by providing facilities that support their lives. In the water area, of course, boats are needed as a mode of transportation for fishermen. Likewise, markers of settled life in the form of settlements with traditional buildings including ‘Rumah Gadang’. This paper uses qualitative methods with inductive reasoning flows. Data was collected on primary (through observation, observation of object and environment, in-depth interviews) and secondary data. The steps in qualitative research are data collection, analysis, and data synthesis. The purpose of writing is to find out about the sustainability of wood culture on the shores of Lake Singkarak and the local wisdom of the community. The change in manufacture and utilization from dugout canoes to plank boats is an adaptation strategy to the scarcity of sources of Surian wood tree materials. The developed buildings and ornaments also depict the complexion of maritime life (in the lake environment). Nature is a source of inspiration in its motifs and coloring, such as the motif of ‘pucuak rabuang’ (young bamboo), flowers, leaves, fish, and the Dutch royal crown. This is a form of local wisdom of the community in adapting to environmental conditions.